2017
DOI: 10.4103/aian.aian_227_17
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors, vascular lesion distribution, outcome and recurrence of strokes due to intracranial atherosclerosis: One year data from Hyderabad stroke registry

Abstract: Background:Intracranial atherosclerotic stenosis (ICAS) is a common cause of ischemic stroke in Asian countries and probably in India.Aim:The aim of this study was to describe the risk factors, distribution of vascular lesions, recurrence and outcome of stroke due to ICAS.Methodology:A total of 100 consecutive patients of ischemic stroke due to ICAS were enrolled prospectively from January 1, 2015, to December 31, 2015, and followed for 1 year for treatment compliance and recurrence. The details about demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Previous studies in China showed that a lack of understanding of the disease made patients fearful, uneasy and uncertain (Benoit et al, 2020). Disease management knowledge helped patients alleviate fear (Fukuoka et al, 2019), prevent disease recurrence and promote physical health (Ram et al, 2017). Therefore, clinicians should closely communicate with patients and their families and provide education about the disease, treatment, rehabilitation and recommended lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in China showed that a lack of understanding of the disease made patients fearful, uneasy and uncertain (Benoit et al, 2020). Disease management knowledge helped patients alleviate fear (Fukuoka et al, 2019), prevent disease recurrence and promote physical health (Ram et al, 2017). Therefore, clinicians should closely communicate with patients and their families and provide education about the disease, treatment, rehabilitation and recommended lifestyles.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes are known to be at higher risk of recurrent stroke due to sICAS, 17,[40][41][42][43][44][45] but there is a lack of compelling evidence to suggest that improved glycemic control results in better outcomes in patients with sICAS in large randomized controlled trials. A retrospective vessel wall magnetic resonance imaging study of 156 patients with 50% to 99% sICAS found diabetes (OR, 1.24 [95% CI, 1.04-3.79]; P=0.018) and enhancement ratios of culprit plaques (OR, 1.94 [95% CI, 1.27-3.09]; P<0.001) to be independently associated with risk of recurrent ischemic stroke.…”
Section: Diabetesmentioning
confidence: 99%